Reflux esophagitis. Pathological bases of a rational therapeutic plan - Bermúdez, Oscar (Cirugía del Uruguay, 2020)
Gastroesophageal reflux always occurs under pathological conditions and creates a pathology at the same time when it fills conditions of aggressiveness. Call it "reflux esophagitis", "is, peptic opgitis", "peptic disease of the esophagus" or "reflux disease", the entity nosological origin that originates in the lower esophagus as a consequence of the aggressive action of the secretions of the upper digestive sector, is, for its pathological polymorphism, a complex condition in the anatomo-functional field, in its clinical expression and in its treatment ...